Determinantes sociais da sífilis no Brasil - Uma revisão de literatura - Costa, Milena Alves de Carvalho (Universidade Federal do Tocantins, 2022)
Syphilis is a sexually transmitted infection - STI, caused by the bacterium Treponema pallidum. A serious consequence of untreated / inadequately treated acquired syphilis is vertical transmission of Treponema. Congenital syphilis represents the fragility of care provided to the population. Understanding the relationships between the determinants and determinants of health conditions and disease in a population is a challenge, translated into models that seek to propose a visualization of the plot of these relationships. In order to contribute to the understanding of the factors associated with the occurrence of syphilis in Brazil in recent years, this study aimed to identify the types of studies, aspects of DS addressed, regional concentration of publications, population studied as well as the determinants most frequently identified . This is an integrative review of the literature. The databases PUBMED, LILACS, BIREME and SCIELO were used in the period from January to March, 2019. The descriptors, according to DeCS and Mesh, were respectively: Social determinants of Health / Social Determinants of Health, syphilis and Treponema infection / syphilis, health profile / Epidemiologic Measurements. A total of 5179 articles were identified, selected for analysis, after reading the title and abstract 191 articles and after exclusion criteria, 44 articles were analyzed. The Northeastern and Southeast regions accounted for the bulk of the publications, 27.27% and 22, 73% respectively, with the North region (6.82%) of the country reporting the least published research on the subject. National studies accounted for 18.18% of publications. Pregnant women, postpartum women and children accounted for the majority of the study population (81.76%). 95% of the productions concerned transverse epidemiological studies. Productivity was analyzed for DS levels following the Dahlgren and Whitehead model: 34.1% of the articles addressed aspects that characterize levels 2, 3 and 4. In 56.8% of the articles, the macro determinants did not appear explicitly. The analysis confirmed that syphilis is a serious public health problem in Brazil, and that it should be addressed more effectively, not only by public health authorities, but also by professionals and the population. Factor prenatal care was related to the increased risk of congenital syphilis and maternal reinfection and in the general population: number of sexual partnerships, use of alcohol and other drugs, non use of condoms in all relationships. Studies that have deepened the analysis of socioeconomic factors and the occurrence of syphilis have shown that poverty and conditions that further undermine the population are significantly associated with the occurrence of syphilis, especially in pregnant women. Thus, it is essential to understand what and how DSs work in the territory for health professionals, since the necessary inputs for diagnosis, treatment and follow-up are available and accessible to professionals, do not present enough to reduce the number of cases. Intersectoral work becomes essential for the development of strategies to address situations that put populations at risk, or worse, keep them at risk with regard to health, and here, in particular, to illness, to Treponema infection.